Non-lethal sonodynamic therapy mitigates hypertensive renal fibrosis through the PI3K/AKT/mTORC1-autophagy pathway - DanDan Liu; Hui Wang; Jialong Li; Siqi Sheng; Shu Wang; Ye Tian (Scientific Reports)
Abstract Hypertension constitutes a significant public health concern, characterized by a high incidence and mortality rate. Hypertensive kidney disease is a prevalent complication associated with hypertension and is the second leading cause of end-stage renal disease (ESRD). Renal fibrosis linked to hypertension has emerged as the third leading cause of disease in dialysis patients. Autophagy activity is crucial for maintaining homeostasis, vitality, and physiological function of kidney cells, while also protecting the kidneys from fibrosis. The deficiency of autophagy will increase the sensitivity of the kidney to the damage, leading to impaired renal function, accumulation of damaged mitochondria and more severe of renal fibrosis. However, enhancing autophagy by activating the PI3K/AKT, AMPK, and mTOR pathways, improves podocyte injury and renal pathological changes, and ameliorates renal function. Current clinical interventions aimed at halting or reversing renal fibrosis in hypertensive patients are notably limited in their efficacy. Here, we present Non-lethal Sonodynamic Therapy (NL-SDT), in which ultrasound is used to activate locally sonosensitizers, thereby stimulating the production of reactive oxygen species for the purpose of modulating cell function or fate, as a novel methodology to inhibit progression of hypertensive renal fibrosis. To confirm whether NL-SDT can reduce hypertensive renal fibrosis and its mechanism. The mice model of hypertensive renal fibrosis was established by using osmotic minipumps (Alzet model 2004, Cupertino, CA) equipped with angiotensin-II (Ang II). The pumps were implanted in mice, ensuring constant infusion of Ang II at a dose of 1.0 µg/kg per minute for 4 weeks. The mice were exposed to 0.4 W/cm2 intensity ultrasonic radiation for 15 min at 4 h post injection of sinoporphyrin sodium (DVDMS) (4 mg/kg) into the caudal vein was repeated weekly for 4 treatments. The kidney from mice was stained with masson’s trichrome staining for collagen fiber expression, while alpha-smooth muscle actin (α-SMA) expression was determined via immunohistochemical staining. The protein levels of fibrosis parameters (α-SMA, collagen I, vimentin), pathway-related proteins (PI3K, AKT, mTORC1) and autophagy-related protein LC3B were determined using western blotting. Intracellular reactive oxygen species (ROS) levels were detected using DCFH-DA probe. Immunofluorescence was also used to observe the expression of α-SMA and E-cadherin in cells. Pathway-related protein inhibitors (the autophagy-related inhibitor 3-methyladenine (3-MA), chloroquine (CQ), ROS inhibitor N-acetyl-L-cysteine (NAC) were applied, and autophagosome changes were observed under transmission electron microscopy. Immunofluorescence was used to observe LC3 spot formation within cells. We obtained the following results via animal and cellular research. In vivo, (1) The collagen area of renal tissue was increased significantly in Ang II group (50.6%). The positive expression of α-SMA was increased significantly (37.8%). (2) The collagen area decreased after NL-SDT treatment (34.8%). The expression of α-SMA was decreased too (48.9%). The expression of LC3B increased in NL-SDT group. (3) The effect of NL-SDT on reducing renal fibrosis can be changed by rapamycin and CQ. In vitro. (1) The expression of α-SMA, collagen I and vimentin were increased significantly in TGF-β1-induced NRK-52E cells. (2) The increase of autophagosomes was observed in TGF-β1-induced NRK-52E cells after NL-SDT. The levels of ROS were increased after NL-SDT (24.8%). The effect of NL-SDT on autophagy was reversed after administration of NAC. The expression of PI3K, P-AKT and P-mTORC1 was decreased in TGF-β1-induced NRK-52E cells after NL-SDT. NL-SDT inhibited the transition of epithelial cells into myofibroblasts by activating PI3K-AKT-mTORC1-autophagy pathway in TGF-β1-induced NRK-52E cells. (3) The administration of the pathway inhibitors showed a reciprocal effect on NL-SDT-inhibited epithelial-mesenchymal transition (EMT). (1) NL-SDT reduced blood pressure temporarily in mice model of hypertensive renal fibrosis induced by Ang II. (2) NL-SDT alleviated renal fibrosis in mice model of hypertensive renal fibrosis induced by Ang II. (3) NL-SDT promoted autophagy by inhibiting PI3K-AKT-mTORC1 signaling pathway and alleviated renal fibrosis in mice model of hypertensive renal fibrosis induced by Ang II. NL-SDT is a non-invasive and efficacious regimen to inhibit renal fibrosis. It may be a new approach for clinical treatment of renal fibrosis, delaying or reducing the occurrence of ESRD.